An aggravated return-to-work case of organic solvent induced chronic toxic encephalopathy - Sangyun Seo; Jungwon Kim (Annals of Occupational and Environmental Medicine, 2018)
Abstract Background Organic solvent-induced chronic toxic encephalopathy (CTE) is known as a non-progressive disorder that does not progress after diagnosis. The authors present a case those symptoms worsened after continued exposure to organic solvent after returning to work. Because such a case has not been reported in South Korea to the best of our knowledge, we intend to report this case along with literature review. Case presentation A 59-year-old man, who performed painting job at a large shipyard for 20 years, was receiving hospital treatment mainly for depression. During the inpatient treatment, severe cognitive impairment was identified, and he visited the occupational and environmental medicine outpatient clinic for assessing work relatedness. In 1984, at the age of 27, he began performing touch-up and spray painting as a shipyard painter. Before that he had not been exposure to any neurotoxic substances. In 2001, at the age of 44, after 15 years of exposure to mixed solvents including toluene, xylene and others, he was diagnosed with CTE International Solvent Workshop (ISW) type 2A. After 7 years of sick leave, he returned to work in 2006. And he repeated return-to-work and sick leave in the same job due to worsening of depressive symptoms. He had worked four times (2006–2010, 2011–2011, 2011–2011, 2016–2017) for a total of 5 years as a shipyard painter after first compensation. During the return-to-work period, the mean values of the mixed solvent index ranged from 0.57 to 2.15, and except for a one semiannual period, all mean values were above the standard value of 1. We excluded other diseases that can cause cognitive impairment like central nervous system diseases, brain injury, psychological diseases and metabolic diseases with physical examinations, laboratory tests, and brain image analysis. And finally, throughout neuropsychological tests, an overall deterioration in cognitive function was identified compared to 2002, and the deterioration types was similar to that often shown in the case of CTE; thus a diagnosis of CTE (ISW) type 3 was made. Conclusion This case is showing that CTE can go on with continued exposure to mixed solvents. Appropriate “fitness to work” should be taken to prevent disease deterioration especially for the sick leave workers.